Correlation analysis of balance function with plantar pressure distribution and gait parameters in patients with cerebral infarction in the basal ganglia region - Sihao Liu; Huixian Yu; Zhaoxia Wang; Pei Dai (Frontiers in Neuroscience, 2023)
ObjectiveTo analyze the correlation between balance function and gait parameters of patients with basal ganglia infarction. And to observe the influence of balance function on plantar pressure and hemiplegia gait based on the Berg Balance Scale (BBS) score.MethodsOne hundred and forty patients with cerebral infarction hemiplegia in the basal ganglia region (a study group, n = 140) and healthy people (a control group, n = 140) were enrolled. The study group was evaluated with the BBS, the 10 m walking test (10MWT), and the timed up-and-go test (TUGT). The gait parameters and the peak plantar pressure were measured in both groups while walking, and the differences between the groups were compared. In addition, the characteristics of the plantar pressure curve of the hemiplegic and non-hemiplegic sides during walking and the correlation between the 10MWT, the TUGT, the plantar pressure peak, the gait parameters,and the BBS score were analyzed in the study group.ResultsThe peak plantar pressure of the forefoot and heel, stride length, lateral symmetry, stand phase, swing phase, and dual stand phase of both sides in the study group were significantly lower than those in the control group (P < 0.05). The BBS score negatively correlated with the 10MWT, the TUGT, the peak plantar pressure of the hemiplegic forefoot, midfoot, and the non-hemiplegic midfoot, the anterior to posterior position (ant/post position), hemiplegic stand phase, and the dual stand phase (P < 0.05). The BBS score positively correlated with the hemiplegic swing phase and stride length (P < 0.05).ConclusionA correlation was found between the forefoot plantar pressure and the stand phase of the hemiplegic limbs, the ant/post position, and the balance function after basal ganglion cerebral infarction. This association can be used in walking and balance assessment for stroke rehabilitation. Correcting forefoot pressure or the front and ant/post position can improve balance function.